(untitled) (Acta Polytechnica CTU Proceedings, 2014)
The galactic center has long been a region of interest for high-energy and very-high-energy observations. Many potential sources of GeV/TeV gamma-ray emission are located in this region, e.g. the accretion of matter onto the central black hole, cosmic rays from a nearby shell-type supernova remnant, or the annihilation of dark matter. The galactic center has been detected at MeV/GeV energies by EGRET and recently by Fermi/LAT. At TeV energies, the galactic center was detected at the level of 4 standard deviations with the Whipple 10m telescope and with one order of magnitude better sensitivity by H.E.S.S. and MAGIC. We present the results from 3 years of VERITAS galactic center observations conducted at large zenith angles. The results are compared to astrophysical models.